2018
DOI: 10.1088/2058-8585/aabc8c
|View full text |Cite
|
Sign up to set email alerts
|

Functional screen printed radio frequency identification tags on flexible substrates, facilitating low-cost and integrated point-of-care diagnostics

Abstract: This work explores the practical functionality of ultra-high frequency (UHF) radio frequency identification (RFID) tags screen printed onto various low-cost, flexible substrates. The need for integrated and automated low-cost point-of-care diagnostic solutions has driven the development of automated sensing and connectivity for implementation with these devices. This work explores wireless communication for paper-based point-of-care diagnostic solutions through screen printing of UHF RFID tags onto various low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…However, one of the main challenges to POC testing is ensuring 87 ). Other manufacturers have developed innovative connectivity solutions that can use mobile phones to read the results from lateral flow assays and provide electronic result exchange, while a third option would be to include connectivity directly onto the test 88 . Ideally, connectivity should not only include collection and transmission of test data, but also analysis to provide feedback for immediate patient treatment or for surveillance.…”
Section: A Look To the Futurementioning
confidence: 99%
“…However, one of the main challenges to POC testing is ensuring 87 ). Other manufacturers have developed innovative connectivity solutions that can use mobile phones to read the results from lateral flow assays and provide electronic result exchange, while a third option would be to include connectivity directly onto the test 88 . Ideally, connectivity should not only include collection and transmission of test data, but also analysis to provide feedback for immediate patient treatment or for surveillance.…”
Section: A Look To the Futurementioning
confidence: 99%
“…Taking devices to Zimbabwe for pilot study use, they have demonstrated it is possible to significantly increase the turnaround time of external assessment testing in remote parts of Africa [85]. An option for handheld PoC devices has been presented by Smith et al whereby a lateral flow assay device is integrated with data specific tags for picture-based data connectivity (see Figure 7) [86]. Environmental awareness is an issue that began in the early 7 th century [87] and has become a central issue in modern-day society, science, and politics [88].…”
Section: Real-time Quantitative Datamentioning
confidence: 99%
“…Research into miniaturization of device design and reagent volume requirements will further environmental friendliness in the future. Furthermore, recent advances in paper-based sensing may provide a suitable platform for biomarker detection in the near future [47,84,86].…”
Section: Real-time Quantitative Datamentioning
confidence: 99%
See 1 more Smart Citation
“…40 The SL900A (AMS, Austria) provides an attractive integrated circuit (IC) solution, with a variety of on-board sensing capabilities, thereby negating the need for additional complex circuitry. Previous printed component development on which this work is based includes the printing of RFID tags with the SL900A onto different flexible substrates, 41 as well as example applications of SL900A RFID tags, including fluidic sensing and temperature readout. 42,43 The passive low-cost reader device is sufficiently low in cost as it can be disposed of after several tens to hundreds of uses, without the need for maintenance.…”
Section: Proposed Solutionmentioning
confidence: 99%